Diseminasi Transformasi Digital: Refleksi Hasil Penelitian pada UMKM Kerajinan Tradisional di Makassar - Yulianto, Harry (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
This dissemination activity aims to share findings and reflections from research on the digital transformation of traditional handicraft MSMEs in Makassar, as well as formulate recommendations for collaborative action. Through a multimodal approach (hybrid seminars, interactive discussions) the activity involved 25 participants. The results show success in knowledge transfer, the creation of direct business opportunities, and the preparation of the digital transformation roadmap and Quintuple Helix collaboration protocol. It is concluded that contextual and participatory dissemination is effective in transforming research findings into real action. The suggestions put forward include the need for a strategy of stakeholder engagement, segmentation of materials based on digital literacy levels, and a long-term impact monitoring system to ensure the sustainability of inclusive digital transformation initiatives based on local wisdom. In addition, it is important to strengthen the capacity of MSME actors through advanced training that focuses on the use of digital marketing technology, product management, and market analytics. The sustainability of collaborative networks between academics, governments, communities, industry players, and the media is also a determining factor in accelerating the digital transformation process in a comprehensive and sustainable manner.